a.
sqrt{1/64}
b.
-sqrt{1/64}
c.
root(3){-1/64}
a. 1/8
b. -1/8
c. -1/4
root{3}{24} - root{3}{56} + root{3}{81}
5 root{3}{3} - 2root{3}{7}
a.
(-125)^(-2/3)
b.
-125^(-2/3)
a. 1/25
b. -1/25
root(3)(3m -2) + 5 = 1
-62/3
a. (3+5i)(3-5i)
b. (3+5i) - (3-5i)
a. 34
b. 10i
Solve:
25y^2 + 16 = 17
1/5, -1/5
(\sqrt{5} + \sqrt{2})^2
7 + 2\sqrt{10}
(27^4)^{-1/3}
1/81
sqrt(5-2k) = k-3
No solution
2 is extraneous
a. - √(15) * √(-25)
b. √(-15) * √(-25)
a. -5i√(15)
b. -5√(15)
a.
sqrt{250}
b.
root(3)(250)
a.
5sqrt{10}
b.
5 root(3)(2)
sqrt{10a} - sqrt{5a}/sqrt{2} + \sqrt{(2a)/5}
(7sqrt{10a})/10
(root(6)(3) * root(3)(3))/root(4)(3)
root(4)(3)
sqrt(2x+5) - 2sqrt(2x) =1
2/9
Solve:
3/4x^2 + 12 =0
4i, -4i
2 sqrt(270a^3b^10)
6ab^5 sqrt{30a}
(5sqrt{6} + 3sqrt{2})(2sqrt{6} - 4\sqrt{3})
60 - 60\sqrt{2} + 12\sqrt{3} - 12\sqrt{6}
root{4}{x}*root(6)(x) \div root(3)(x)
x^(1/12)
5x = x sqrt(2) + 9
(45 + 9 sqrt{2})/23
a.
i^45
b.
i^91
c.
i^68
a. i
b. -i
c. 1
a.
sqrt{3/8}
b.
root{4}{3/8}
a.
sqrt{6}/4
b.
root{4}{6}/2
(2\sqrt{7} - \sqrt{3})/(\sqrt{7} + \sqrt{3})
(17 - 3sqrt(21))/4
(x^2+4)^{2/3} + 1 = 26
11, -11
sqrt{3y+4} = 2 + sqrt{y+2}
y = 7
-1 is extraneous
(2+5i)/(sqrt{3}+\sqrt{6}i)
(2 \sqrt{3} + 5\sqrt{6})/9 +(-2\sqrt{6} + 5\sqrt{3})/9i
root(3)(6c) * root(3)(8c^-5)
(2root(3)(6c^2))/c^2
\sqrt{x}/(\sqrt{x}+ \sqrt{y}) + \sqrt{y}/(\sqrt{x} - \sqrt{y})
(x+y)/(x-y)
Show that 2+i is a solution to
x^2 -4x + 5 =0
(2+i)^2 -4(2+i) + 5 =0
3 + 4i -8 -4i + 5 =0
0 = 0